2022
DOI: 10.1155/2022/6940715
|View full text |Cite|
|
Sign up to set email alerts
|

Meta-Analysis on the Application Value of Collaborative Nursing in Postcolostomy Nursing of Patients with Colorectal Cancer

Abstract: Objective. To systematically evaluate the effect of collaborative nursing on self-care ability of postcolostomy patients with colorectal cancer (CRC). Methods. PubMed, Web of Science, Embase, China National Knowledge Infrastructure, and Wanfang databases were searched to collect relevant literatures on randomized controlled trials of postcolostomy patients with CRC. The search period was started from 2010 to 2021. Statistical analysis was performed on the data extracted from the comprehensive meta-analysis wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The analysis of the reasons may be that the patient is tormented by the disease before surgery and the fear of the unknown operation, coupled with being in the unfamiliar environment of the hospital, which brings a strong impact on the patient's psychology and cannot adapt well, and with the extension of the postoperative time, with the professional support of medical staff, the patient gradually adapts to the disease and the existence of the stoma, coupled with the support from the family, the patient's confidence is enhanced and the psychological toughness is improved [22,23] ; 3 months after discharge. It is explained that through psychological nursing combined with extended care, the training of coping skills for patients can reduce the negative psychological stress response caused by the emergence of unfamiliar environment and stoma, face the disease problem in a positive coping way, enhance their own measures and skills for handling emergencies, effectively control the adverse reactions caused by stressors, [24][25][26] improve their psychological resilience, and improve their self-care ability.…”
Section: Group Hama Hamdmentioning
confidence: 99%
“…The analysis of the reasons may be that the patient is tormented by the disease before surgery and the fear of the unknown operation, coupled with being in the unfamiliar environment of the hospital, which brings a strong impact on the patient's psychology and cannot adapt well, and with the extension of the postoperative time, with the professional support of medical staff, the patient gradually adapts to the disease and the existence of the stoma, coupled with the support from the family, the patient's confidence is enhanced and the psychological toughness is improved [22,23] ; 3 months after discharge. It is explained that through psychological nursing combined with extended care, the training of coping skills for patients can reduce the negative psychological stress response caused by the emergence of unfamiliar environment and stoma, face the disease problem in a positive coping way, enhance their own measures and skills for handling emergencies, effectively control the adverse reactions caused by stressors, [24][25][26] improve their psychological resilience, and improve their self-care ability.…”
Section: Group Hama Hamdmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%